Re-tensioning Anterior Cruciate Ligament Reconstruction Using an Adjustable Femoral Button - José Leonardo Rocha de Faria MD, MSc; Douglas Mello Pavão MD, MSc, PhD; Rafael Erthal de Paula MD, MSc; João Mateus Paravidino MD; Conrado Torres Laett PhD; Dângelo José de Andrade Alexandre PhD; Daniel Ramallo MD, MSc; Rodrigo Sattamini Pires e Albuquerque MD, PhD; Phelippe Valente Maia MD, MSc; Alan de Paula Mozella MD, MSc, PhD (SAGE Publishing, 2023)
Background: Despite advancements in surgical techniques for anterior cruciate ligament (ACL) treatment, persistent functional impairment, reduced quality of life, and limited physical activity participation continue to be common after postoperative rehabilitation. We modify the traditional ACL reconstruction method by using hamstring tendons grafts and re-tensioning them. Indications: This procedure is indicated for patients undergoing ACL reconstruction surgery with soft tissue grafts, utilizing femoral fixation with an adjustable button and tibial fixation with an interference screw. Technique Description: We employ hamstring grafts for ACL reconstruction and perform femoral fixation using an adjustable button. Initially, we pull the graft approximately 10 mm less than the length of the thickest tunnel drill. This allows for subsequent graft traction after tibial fixation. Following tibial fixation, we pull the graft proximally, inserting it a few millimeters further into the femoral tunnel. This re-tensioning increases tension and enhances physical examination results. In addition, we incorporate the braid graft technique to augment the graft's final thickness. Results: This technique yields reduced postoperative residual laxity during physical examinations. Our institution's ethics committee is currently reviewing a clinical study comparing functional outcomes with traditional techniques. Discussion/Conclusion: The ACL re-tensioning technique is easily implemented and involves a subtle modification to the traditional approach, allowing for graft re-tensioning and diminishing the risk of residual laxity post-interference screw fixation. This approach acknowledges that insertion of the interference screw can inadvertently reduce graft tension, counteracting the tension applied during fixation. Consequently, this technique is expected to yield superior clinical outcomes.